HI-TECH BUSINESS IN ECONOMICALLY DEVELOPED COUNTRIES AND ITS INTEGRATION MECHANISM - V. N. Voronina (Модернизация, инновация, развитие)
In the hi-tech sphere, business integration forms widely wary. Particularly interesting is a way of such integration practiced in Japan through associations called «keiretsu» whose functioning mechanism is considered in detail. Specific features of this approach make it advantageous incomparison to classic western firm integration ways. Still, experiences gained in USA and some European countries, particularly in Finland, are of interest for Russian hi-tech business too.